2020
DOI: 10.1021/acsnano.0c04492
|View full text |Cite
|
Sign up to set email alerts
|

Direct Visualization of Current-Stimulated Oxygen Migration in YBa2Cu3O7−δ Thin Films

Abstract: The last years have witnessed major advancements in all-electrical doping control on cuprates. In the vast majority of cases, the tuning of charge carrier density has been achieved via electric eld eect by means of either a ferroelectric polarization or by using a dielectric or electrolyte gating. Unfortunately, these approaches are constrained to rather thin superconducting layers and require large electric elds in order 1 to ensure sizable carrier modulations. In this work, we focus on the investigation of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…Our resistor network simulations show that the insulating barrier that forms during the M → I volatile switching concentrates not only the dissipated power but also the applied voltage. It is possible that the transverse barrier formation can occur in systems which feature a nonvolatile low-to-high-resistance switching caused by ion electromigration, such as rare-earth nickelates 77,78 , manganites [77][78][79][80][81][82] , and cuprates 77,79,83 . In fact, spatial patterns previously reported for the nonvolatile switching in YBa 2 Cu 3 O 7 83 , LSMO 84 and in NdNiO 3 85 can be rationalized by considering the tendency of low-to high-resistance switching to occur by the formation of a transverse insulating barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Our resistor network simulations show that the insulating barrier that forms during the M → I volatile switching concentrates not only the dissipated power but also the applied voltage. It is possible that the transverse barrier formation can occur in systems which feature a nonvolatile low-to-high-resistance switching caused by ion electromigration, such as rare-earth nickelates 77,78 , manganites [77][78][79][80][81][82] , and cuprates 77,79,83 . In fact, spatial patterns previously reported for the nonvolatile switching in YBa 2 Cu 3 O 7 83 , LSMO 84 and in NdNiO 3 85 can be rationalized by considering the tendency of low-to high-resistance switching to occur by the formation of a transverse insulating barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the mechanism behind these changes in the oxygen content and ordering is a key point in controlling the final superconducting properties of the CCs. Besides, it will also allow a better comprehension of other phenomena related with the oxygen content in REBCO films as, for example, the resistive switching. , …”
Section: Introductionmentioning
confidence: 99%
“…Besides, it will also allow a better comprehension of other phenomena related with the oxygen content in REBCO films as, for example, the resistive switching. 9,10 Within the family of REBCO, YBa 2 Cu 3 O 7−δ (YBCO) is probably the best-known and -studied compound since it was the first superconductor showing a T c above liquid-nitrogen temperature (LN 2 , 77 K). However, there are other REBCO compounds that could exhibit better electrical properties than YBCO aside from small improvements in T c and, therefore, be very attractive materials to be studied in depth.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In ref. [13] it has been shown that after electromigration part of the bridge becomes deoxygenated down to a certain minimum value x min whereas other zones are oxygenated up to an upper value x max . This can be understood as a consequence of a concentration‐dependent activation energy E a ( x ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a radically different approach consisting in current‐induced migration of oxygen, has been proposed. [ 13 ] This technique has been implemented to scan the entire temperature‐hole concentration phase diagram in a single sample. [ 14 ] In this case, the agglomeration of oxygen vacancies manifests itself as a zone of higher reflectivity thus permitting to track the temporal evolution of the affected area by optical microscopy.…”
Section: Introductionmentioning
confidence: 99%